First spine surgery utilizing real-time image-guided robotic assistance. Issue 1 (1st January 2019) - Ahmed, A. Karim; Zygourakis, Corinna C.; Kalb, Samuel; Zhu, Alex M.; Molina, Camilo A.; Jiang, Bowen; Blitz, Ari M.; Bydon, Ali; Crawford, Neil R.; Theodore, Nicholas
Abstract: Robotics in spinal surgery has significant potential benefits for both surgeons and patients, including reduced surgeon fatigue, improved screw accuracy, decreased radiation exposure, greater options for minimally invasive surgery, and less time required to train residents on techniques that can have steep learning curves. However, previous robotic systems have several drawbacks, which are addressed by the innovative ExcelsiusGPS TM robotic system. The robot is secured to the operating room floor, not the patient. It has a rigid external arm that facilitates direct transpedicular drilling and screw placement, without requiring K-wires. In addition, the ExcelsisuGPS TM has integrated neuronavigation, not present in other systems. It also has surveillance marker that immediately alerts the surgeon in the event of loss of registration, and a lateral force meter to alert the surgeon in the event of skiving. Here, we present the first spinal surgery performed with the assistance of this newly approved robot. The surgery was performed with excellent screw placement, minimal radiation exposure to the patient and surgeon, and the patient had a favorable outcome. We report the first operative case with the ExcelsisuGPS TM, and the first spine surgery utilizing real-time image-guided robotic assistance.